Influence of polypharmacy and use of inappropriate medication for the elderly on the glomerular filtration rate (Research, Society and Development, 2021)
Objective: To investigate the association between the change in the estimated Glomerular Filtration Rate in elderly people with the use of Potentially Inappropriate Medicines for the elderly and polypharmacy. Methodology: Cross-sectional and analytical study based on data from 1216 elderly users of the Public Health System who had estimated Glomerular Filtration Rate  exams, the same being considered altered when